Mecp2 regulates tnfa during zebrafish embryonic development and acute inflammation - M. van der Vaart; O. Svoboda; B. G. Weijts; R. Espín-Palazón; V. Sapp; T. Pietri; M. Bagnat; A. R. Muotri; D. Traver (Disease Models & Mechanisms, 2017)
Mutations in MECP2 cause Rett syndrome, a severe neurological disorder with autism-like features. Duplication of MECP2 also causes severe neuropathology. Both diseases display immunological abnormalities that suggest a role for MECP2 in controlling immune and inflammatory responses. Here, we used mecp2-null zebrafish to study the potential function of Mecp2 as an immunological regulator. Mecp2 deficiency resulted in an increase in neutrophil infiltration and upregulated expression of the pro- and anti-inflammatory cytokines Il1b and Il10 as a secondary response to disturbances in tissue homeostasis. By contrast, expression of the proinflammatory cytokine tumor necrosis factor alpha (Tnfa) was consistently downregulated in mecp2-null animals during development, representing the earliest developmental phenotype described for MECP2 deficiency to date. Expression of tnfa was unresponsive to inflammatory stimulation, and was partially restored by re-expression of functional mecp2. Thus, Mecp2 is required for tnfa expression during zebrafish development and inflammation. Finally, RNA sequencing of mecp2-null embryos revealed dysregulated processes predictive for Rett syndrome phenotypes.